USING WORDWALL TO IMPROVE STUDENTS’ WRITING PROCEDURE TEXT - Siti Fauziyah, Siti Fauziyah; Chasanah, Zulia; Johan, Andrian Nuriza (ENGLISH, 2025)
This study aims to examine the effectiveness of Wordwall as a digital learning tool to improve students' writing skills in procedure texts. Using a quasi-experimental design, the study involved 72 tenth-grade students at SMA Negeri 8 Purworejo, divided into an experimental group (using Wordwall) and a control group (traditional methods). Data collection involved pre-tests, treatment, post-tests, and statistical analysis using SPSS 25. The findings revealed that students in the experimental group showed significant improvement, with their mean post-test score increasing to 80.00, compared to 68.42 in the control group. The paired sample t-test results indicated a significant difference in the writing performance of students exposed to Wordwall-based learning (p = 0.000 < 0.05). Students in the experimental group established higher engagement and motivation. These results suggest that Wordwall effectively enhances students' writing abilities, particularly in structuring and organizing procedure texts. Integrating game-based digital platforms like Wordwall in language learning can positively impact students' writing performance and motivation.